"¡Maguer que a algunos pesa, mejores sodes que nós!": las virtudes de la cortesía en el Poema de Mío Cid - Erica Janin (Medievalia)
"¡Maguer que a algunos pesa, mejores sodes que nós!": las virtudes de la cortesía en el Poema de Mío Cid